Calcium Levels in the Maxillae of Human Foetuses - Farah,Ghaus (Sociedad Chilena de Anatomía, 2011)
Calcium along with phosphorus and carbonate imparts hardness and strength to skeletal system. Most of the human studies in this context are based on informations in postnatal life. There are different theories to explain the manner in which the matrix of bone becomes impregnated with the two inorganic salts, calcium phosphate and calcium carbonate. In our study, 29 human foetuses were obtained from the museum section of Department of Anatomy, J .N. Medical College, Aligarh, and divided into five groups. Maxillae were cleaned by separating the soft tissue and dissolved in concentrated nitric acid to determine calcium. Results were analysed by using Student's 't' test. The most striking feature of our findings was a reduction in aforementioned relative calcium in subsequent groups of foetuses. This decrease was highly significant in foetuses of last three groups i.e. III, IV and V. On the other hand, when total amount of calcium in foetal maxillae of adjacent groups were compared, a steady rise in concentration of calcium was noticed but no definite pattern was observed. Sexual dimorphism could be considered only in groups IV and V foetuses due to lack of female foetuses in first three groups. Some scientists did consider the human foetal bones but their interests were confined to parietal bone, femur and teeth. None of the earlier studies considered calcium concentration in maxillae of human foetuses. Therefore, our study aimed at measuring the level of calcium in maxillae of developing human foetuses in different age groups to find pattern, if any, during development for medicolegal purposes.